Modelos de geração de viagens para condomínios residenciais horizontais - Torquato, Tiago Lourenço de Lima (2013)
The meeting of man need s, in the urban environment, create different types of projects, which significantly change city s life. According to the number of dislocations generated, luxury condos are characterized as Trip Generation Polo. Thus, to approve and begin the construction, become necessary preliminary studies, based on the forecast trip production and attraction to determine and minimize their impact on the region where they are installed. There are few studies in Brazil, so, this research intends to build a model about luxury condos trip generation. The case of study was based on the reality of the city of Bauru, São Paulo. The proposed procedure was applied in seven condos with similar characteristics, in which the data were collected from 6:30am to 20pm. This research generated 14 satisfactory models, depending on how trips were made (Cars, on foot and all modes), on the collection period (7h to 9h, 16h to 18h and 6h30 to 20h) and the explanatory variable of the phenomenon (Occupied units and total area of the project). The occupied units were the explanatory variable with better representation of the phenomenon (resulted in lower standard deviations and highest coefficients of determination R²). These results could be basis for future of urban planners, especially in decision-making regarding the approval of new projects. The study is based on quantitative technical procedures of bibliographic research and data collection.